A survey of doctrinal debates on “the general principles of law recognized by civilized nations - BÜYÜK, MEHMET EMİN (My University, 2019)
Article 38/1-c of the Statute of International Court of Justice qualifies the “general principles of law recognized by civilized nations” as one of the three main sources of international law which the Court will apply. Compared to the other two sources, namely international treaties and international custom, general principles of law have been the subject of a much more intense doctrinal controversy. This debates started with the inclusion of general principles of law in the Statute of the Permanent Court of International Justice as a third source by the Advisory Committee of Jurists during travaux préparatoires of the Statute and still continues. This study is an effort to collect and comprehend these doctrinal controversies. For this purpose, first, the discussions in the Advisory Committee of Jurists when drafting the Statute which can be used as a supplementary mean of interpretation and later, the controversy among international lawyers and their thoughts which I think derived mostly from the prejudgments of their authors about the binding nature of international law and their approaches to the jurisprudence of this field have been dealt. As a result, the functions of general principles of law can be described in three different categories: They can be used for providing a framework for interpreting, defining, and implementing other sources. Secondly, they can be used as a material source of the other two sources. Finally, in order to avoid non liquetin international law, where the other rules are not available, these general principles appear as substitute sources.

Uluslararası Adalet Divanı Statüsünün 38/1-c maddesi, “medeni milletlerce tanınmış hukukun genel ilkeleri”ni, Divan’ın kendisine sunulan uyuşmazlıkları çözerken kullanacağı üç temel kaynaktan biri olarak nitelendirmektedir. Diğer iki kaynakla, yani uluslararası andlaşmalar ve uluslararası teamülle karşılaştırıldığında, genel hukuk ilkeleri, çok daha yoğun bir doktrinel ihtilafın konusu olmuştur. Bu tartışmalar, Statü’nün hazırlık çalışmaları sırasında Hukukçular Komitesi tarafından genel hukuk ilkelerinin üçüncü kaynak olarak Uluslararası Daimi Adalet Divanı Statüsü’ne eklenmesiyle başlamış̧ ve hala sürmektedir. Bu çalışma, bu kavramın ve tartışmaların anlaşılması çabasıdır. Bu amaca yönelik olarak, ilk olarak, Hukukçular Komitesi’nde Statü hazırlanırken ortaya konulan, yardımcı yorum aracı olarak kullanılabilecek, tartışmalar ve daha sonra, uluslararası hukukçular arasındaki ihtilaf ve bunların düşünceleri -ki bunlar çoğu zaman uluslararası hukukun bağlayıcılığına ilişkin bu kişilerin ön kabullerinden ve bu alana dair hukuk ilmine yaklaşımlarından doğmaktadır- ele alınmıştır. Sonuç olarak, hukukun genel ilkelerinin işlevleri üç kategori altında değerlendirilebilir: Diğer kaynakların yorumlanması, tanımlanması ve uygulanması konusunda bir çerçeve sunabilirler. İkinci olarak, diğer iki kaynağın maddi kaynakları olarak kullanılabilirler. Son olarak, diğer kaynakların uygun olmadığı durumda, uluslararası hukukta non liquetten kaçınabilmek için bu genel ilkeler ikame kaynak olarak kullanılabilir.
Medeni milletlerce tanınmış hukukun genel ilkeleri”ne dair doktrin tartişmalarına ilişkin bir inceleme
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Devletler Umumi Hukuku; Social Sciences and Humanities; Law; International Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Social Sciences & Humanities; General Principles of Law Recognized by Civilized Nations; Sources of International Law; International Court of Justice; Statute of the Court; Uluslararası Hukukun Kaynakları; Uluslararası Adalet Divanı Statüsü; Medeni Milletlerce Tanınmış Hukukun Genel İlkeleri; Genel Hukuk İlkeleri